The polemic between Leonard Nelson and Ernst Cassirer on the critical method in the philosophy - Kubalica, Tomasz (Folia Philosophica, 2016)
The subject of the paper is a polemic between Leonard Nelson and Ernst Cassirer mainly concerning the understanding of the critical method in philosophy. Nelson refutes the accusation of psychologism and attacks the core of the philosophy of the Marburg School of New-Kantianism. In response to those allegations, Cassirer feels obliged to defend the position of his masters and performs this task brilliantly. The present paper considers similarities and differences in the positions of both sides in this polemic. I try to evaluate the arguments of both sides. I argue that both sides took basically the same positions and existing discrepancies did not justify such an intense polemic. If the disputing sides had approached the discussions in a less emotional way, it could have led to substantive and interesting conclusions.